The effect of live chlorella suspension on the growth and development of grafted seedlings of Cabernet Sauvignon grapes - Natalia Zelenіanska; Iryna Ishchenko; Tetyana Kundilovska; Olesia Mandych (Наукові горизонти, 2023)
One of the ways to grow high-quality grafted grape seedlings is to use modern, environmentally friendly biologically active preparations. Today, such preparations include live chlorella suspension. Its use in grape nursery is a new and relevant technological method of growing planting material. The aim of the study was to show the effect of live chlorella suspension on the realization of the biological potential of grapevines, with the subsequent production of high-quality grafted grape seedlings. Field (recording of plant growth and development), laboratory (determination of quantitative and qualitative parameters of plants) and statistical (confirmation of the reliability of the results) research methods were used. The obtained results showed that for soaking rootstock and scion components it is advisable to use the strain Chlorella vulgaris Beijer, dilution 1:5, soaking should be carried out for 72 hours – rootstock components, 18 hours – scion components; for irrigation of grape garden plot it is advisable to use the strain Chlorella vulgaris Beijer. + Ge, dilution 1:5, it was carried out immediately after planting scions and three times during the growing season – in June, July, and August. The use of these strains of live chlorella suspension allowed obtaining a higher yield of standard seedlings from the garden plot, the plants had a well-developed root system and annual growth. Compared to the control, which was water, the total number of roots increased. Plants in these variants were also characterized by increased growth of the aboveground part. Indicators of total and mature growth, which characterize the overall development of grafted grape seedlings, were in the range of 687.1-773.2 cm3 (total growth volume), 337.9-386.6 cm3 (mature growth volume), while 730.1 and 362.6 cm3 , respectively, in the control. The records of the output of standard seedlings from the garden plot also showed the advantage of using a suspension of live chlorella (an increase of 19.0-21.0%) compared to water. The above technological methods allow obtaining high-quality grape seedling products and can be a promising alternative for more sustainable and environmentally friendly agricultural methods